PENGARUH KONFLIK KERJA, KEPEMIMPINAN, LINGKUNGAN KERJA, TERHADAP STRES KERJA PT. KARSA BIJAK SEMESTA - JEFFREY STANLEY; Syahrian Syahrian (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
The purpose of this study was to analyze and determine the effect of work conflict, leadership and work environment on work stress. The form of research used is causality research. The population used in this study were all employees of PT. Karsa Bijak Semesta as many as 91 employees. This study uses a saturated sampling technique involving 91 employees of PT. Karsa Bijak Semesta as a respondent. The technique used for data collection is using a questionnaire with a Likert scale. The method of analysis in this study using multiple regression analysis. The result of this study is that work conflict has a positive and significant effect on work stress, while leadership and work environment do not have a significant effect on work stress.